Analysis of Indonesia’s Gross Domestic Product Review of Macroeconomic Variables - Aida, Neli; Musyaffa, Irfan (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
First, the impact of family spending; second, the effect of state debt; and third, the effect of zakat revenue on Indonesia's GDP are the goals of this research. The information used for this research is derived from secondary sources, including the websites of the Indonesian Statistics Center, the National Amil Zakat Agency, and the Ministry of Finance. A total of forty observations were gathered from these sources between 2012 and 2021. This research made use of statistical analysis techniques and the Error Correction Model (ECM) for its analysis. For the period 2012-2021, at the 0.000 level of significance, the results show that household spending, state debt, and zakat earnings all have a positive effect on Indonesia's GDP. On the other hand, zakat revenue is a short-term variable that significantly affects Indonesia's GDP from 2012 to 2021, while partially state debt has no long-term or short-term influence. R2 = 0.7997, or 79.97 percent, is the coefficient of determination.